Rural Governance in the UK : Towards a Sustainable and Equitable Society. - Attorp, Adrienne. (Routledge Studies in Sustainability Series, 2022)
This book provides a multidisciplinary analysis of rural society in a post-Brexit UK by examining the emergence of new environmental and rural policies and the implications of this transition for rural communities.